Management of Apnoea in Extremely Preterm Infants: A European Survey - Lavizzari, Anna; Hutten, G. Jeroen; Heiring, Christian; Van De Loo; Moniek; Onland, Wes; Alonso-Ojembarrena, Almudena; Ehrhardt, Harald; Cetinkaya, Merih; Szczapa, Tomasz; Sartorius, Victor; Rocha, Gustavo; et al. (Karger Publishers, 2026)
Introduction: Episodes of apnoea are common in extremely preterm infants (EPIs) and usually treated with caffeine and respiratory support. Understanding differences in apnoea definitions, monitoring practices, and use of respiratory stimulants is essential to improve future treatment.
Methods: Between March and July 2024, one lead consultant at European tertiary neonatal intensive care units (NICUs) was invited to complete a web-based survey on respiratory practices in EPIs. We sought information how they defined apnoea and monitored for it, and how they treated it with caffeine, doxapram, and non-invasive respiratory support.
Results: We received replies from 447/721 (62%) NICUs across 24 European countries. Most NICUs (74%) use both electrocardiogram electrodes and pulse oximetry for apnoea monitoring. All NICUs reported using caffeine citrate, with 102 centres (23%) starting it in the delivery room. The median loading, maintenance and maximum maintenance doses used are 20 mg/kg, 5 and 10 mg/kg/day, respectively. Caffeine is occasionally given twice daily in some NICUs (30%) and stopped at 34–35 weeks of postmenstrual age at most of them (74%). Doxapram is used at 111 (25%) NICUs, with geographical differences. Strategies for the use and escalation of non-invasive respiratory support in case of persistent apnoea are not clearly defined. Automatic closed-loop oxygen delivery is used at 25% of NICUs.
Conclusion: Despite consistency in the dosing and weaning of caffeine, there is much variation in the management of apnoea in preterm infants across Europe. Future research should focus on timing and dosage of caffeine, the use of doxapram, and strategies for optimising non-invasive respiratory support.